O-156 Fertilization rate as a novel indicator for cumulative live birth rate: multicenter retrospective cohort study of 9, 394 complete IVF cycles. (6th August 2021) - Zaca', C; Scaravelli, G; Setti, P.E. Levi; Livi, C; Ubaldi, F M; Villani, M T; Greco, E; Coccia, M E; Revelli, A; Ricci, G; Fusi, F; Vigiliano, V; et al.
Abstract: Study question: Does fertilization rate (FR) affect cumulative success rates in assisted reproduction cycles? Summary answer: These data indicate a positive association between FR with CLBR suggesting the predictive clinical relevance of this parameter and its adoption as Key Performance Indicator(KPI). What is known already: Numerous studies have aimed at characterizing outcome predictors. Maternal age is historically and correctly recognized as the single most important factor impacting on the clinical outcome of ART. More recently ovarian response has also gained interest in this respect. However, the quest for novel, more comprehensive predictive factors is not over; new relevant evidence is starting to emerge. FR is a noteworthy parameter because expressing a fundamental aspect of both oocyte and sperm developmental competence. In fact it has been adopted as a key performance indicator of the IVF laboratory, to assess laboratory, operator, and gamete competence. Study design, size, duration: Reported data concern a retrospective cohort study carried out between 2015 to 2017 involving 7, 968 couples undergoing 9, 394 complete ICSI cycles, i.e. whose all embryos were transferred or disposed.All women aged between 18-42 years were included.We excluded from analysis: surgical sperm retrieval cases, cycles resulting in neither fresh or frozen–thawed embryo transfers, cycles in which live birth were not achieved, but with remaining cryopreserved embryos, cycles of PGT, cycle with fertilization failure and standard IVF cycles. Participants/materials, setting, methods: The cohort was groupped according to fertilization rate intervals based on recommendations of the Vienna Consensus (<65% - Group 1; 65%-80% - Group 2; >80% - Group 3). Harnessing the large size of the original dataset, further cycle stratifications were carried out based on female age (<34, 35-38, 39-42 years) and number of oocytes retrieved (5-7, 8-10, >10 oocytes). Main results and the role of chance: No significant difference in female age was observed between fertilization rate groups (p = 0.640). CLBR was progressively higher in relation fertilization rate in Groups 1, 2 and 3 (20.1%, 34.7%, 41.3%, P < 0.001, respectively). Number of recovered oocytes, embryo number per cycle, cumulative pregnancy rate followed the same trend (p < 0.001). The decrease in CLBR with increasing female age was significantly correlated with fertilization rate and CLBR in all three female age groups (P < 0.001). Finally, to further control for possible patient-specific confounding factors, maternal age, number of retrieved oocytes, percent of inseminated oocytes and fertilization rate were evaluated in a multivariate logistic regression analysis. From this assessment, fertilization rate emerged as a factor independently associated with cumulative live birth rate, to a degree equivalent or higher compared with the number or retrieved oocytes. Limitations, reasons for caution: The study design is retrospective and requires further refinement to control for factors that may impact clinical outcome. Wider implications of the findings: These data indicate a positive association of FR with CLBR, thereby suggesting that fertilization, in addition to representing an assay for gamete quality and laboratory performance, has an independent clinical significance.Irrespective of the number of retrieved oocytes and female age, we observed that, rates of FR are positively associated with CLBR. Trial registration number: None